Dave at night - Levine, Gail Carson (New York : HarperCollins, 1999)
When orphaned Dave is sent to the Hebrew Home for Boys where he is treated cruelly, he sneaks out at night and is welcomed into the music- and culture-filled world of the Harlem Renaissance.
Wilson's Children.
Wilson's Junior High School.
School Library Journal starred.
3.6
3-6
550L
Keywords: Orphans -- Fiction; Jews -- New York (State) -- New York -- Fiction; Harlem Renaissance -- Fiction; African Americans -- New York (State) -- New York -- Fiction; Orphans -- Fiction; Jews -- New York (N.Y.) -- Fiction; Harlem Renaissance -- Fiction; African Americans -- New York (N.Y.) -- Fiction; Orphans -- Fiction; Jews -- Fiction; Harlem Renaissance -- Fiction; African Americans -- Fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction